7×+3(2×-1)=10×+9 si 2(×-3)-13=×-21; 5×+3(×-6)=7×+13 si 6×+4(×-8)=9×+21 Rezolvați ecuatiile
Răspunsuri la întrebare
Răspuns de
1
a)7x+6x-3=10x+9 3x=12 x=4
b)2x-6-13=x-21 x=-2
c)5x+3x-18=7x+13 x=31
d)6x+4x-32=9x+21 x=53
b)2x-6-13=x-21 x=-2
c)5x+3x-18=7x+13 x=31
d)6x+4x-32=9x+21 x=53
Alte întrebări interesante
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă
Matematică,
9 ani în urmă